COVID-19 and cardiovascular consequences: Is the endothelial dysfunction the hardest challenge? (2020)
A Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) has become a pandemic disease named Coronavirus Disease-19 (COVID-19) of epochal dimension. The clinical spectrum of COVID-19 is wide, ranging from asymptomatic forms to severe pneumonia, sepsis and multiple organ dysfunction syndromes resulting in poor outcomes. Among the various consequences of severe COVID-19, cardiovascular (CV) collapse appears the most serious and potentially lethal. On the other hand, pre-existent CV comorbidities are also associated with higher mortality. The most reliable hypothetical pathogenetic mechanism for CV complications and cardiac injury in severe COVID-19 patients appears to be a sustained endothelial dysfunction, caused by the interplay of inflammation and coagulation. In this review, we survey papers addressing issues related to severe COVID-19, characterized by enhanced lung microvascular loss, hypercytokinemia, hypoxemia and thrombosis. We discuss about how the virus-induced downregulation of the angiotensin converting enzyme-2 (ACE2) receptor, used to enter the host cell, could affect the renin-angiotensin system, attempting to clarify the doubts about the use of ACE inhibitors and Angiotensin-II receptor blockers in COVID-19 patients. Finally, we point out how the delicate and physiological homeostatic function of the endothelium, which turns into a disastrous battlefield of the complex interaction between “cytokine and coagulative storms”, can be irreparably compromised and result in systemic inflammatory complications.